Effect of Temperature on the I-V Characteristics of a Polycrystalline Solar Cell - Karki, Indra Bahadur (Journal of Nepal Physical Society, 2016)
The present paper reports the temperature dependencies of full-spectrum photovoltaic parameters for poly-crystalline PV module. The measurements were performed under outdoor environment conditions. The most interesting feature that was observed for these devices was that above a cell temperature of 20°C the positive temperature coefficient observed for the short-circuit current exceeds in magnitude the negative temperature coefficient that was found for the open-circuit voltage. This means that, unlike the situation for conventional PV devices, these cells actually exhibit decrease in efficiency with increasing temperature (reaching a value of 0.05 % at 60°C). Journal of Nepal Physical Society Vol.3(1) 2015: 35-40